Effect of age and cycloplegia on the morphology of the human crystalline lens: swept-source OCT study. Issue 1 (January 2022) - Li, Zhangliang; Qu, Wenyong; Huang, Jinhai; Meng, Ziqi; Li, Xiuyuan; Zou, Rui; Zhao, Yune
Abstract : The crystalline lens revealed steepening anterior surface and increasing equatorial diameter with age. Cycloplegia caused significant changes on the anterior surface, and this effect weakened with age. Abstract : Purpose: To evaluate the effect of age and cycloplegia on the morphology of the crystalline lens using a swept-source optical coherence tomography (SS-OCT) system. Setting: Hospital. Design: Prospective cross-sectional study. Methods: The parameters including anterior chamber depth (ACD), the radii of curvature of the anterior and posterior surface of the crystalline lens (ALR and PLR), lens thickness (LT), lens equatorial diameter (LED), and lens vault (LV) were quantified by the SS-OCT before and after cycloplegia. The paired t test was used to compare the parameters before and after cycloplegia. A multivariate linear regression model was built to analyze the association between the parameters/cycloplegia-induced changes and age, while adjusting for the effect of axial length, refractive status, and sex. Results: 76 individuals (age range, 18 to 86 years) were recruited. The ALR and ACD were negatively correlated with age ( P ≤ .002), and the LT, LV, and LED were positively correlated with age ( P ≤ .004). In participants younger than 60 years, the ALR and ACD significantly increased, whereas the LV and LT significantly decreased after cycloplegia (all P < .001). With aging, cycloplegia-induced differences of ALR ( P = .001) and ACD ( P = .014) significantly decreased, and of LT ( P < .001), LT ( P < .001), and LV ( P = .001) significantly increased. Conclusions: The crystalline lens morphology measured by the SS-OCT revealed steepening anterior surface and increasing equatorial diameter with age. Cycloplegia caused a significant change of anterior surface morphology in participants younger than 60 years, and this effect diminished with age.